Midaortic syndrome with IgA nephropathy in a child: a case report - Shen, Anna; Shen, Li; Li, Wenyan; Cai, Huaiqing; Zheng, Weihua; Huang, Wenyan; Zhang, Rufang; Kang, Yulin (Frontiers in Medicine, 2025)
BackgroundIgA nephropathy (IgAN) is one of the most common glomerulonephritis characterized by deposition of IgA immune complex in the mesangial region and mesangial proliferation in children. It could progress to end stage renal disease. The underlying mechanism of IgAN is not fully understood. It has been known that IgAN could be secondary to autoimmune disorders, respiratory tract diseases, neoplasia, infection, gastrointestinal and liver diseases. Midaortic syndrome (MAS) is characterized by narrowing or occlusion of the distal thoracoabdominal aorta and the openings of its major branches, which may lead to organ damage like heart failure, renal dysfunction and even death. It may be congenital (present at birth) or acquired later in life. So far, no cases of IgAN concomitant with MAS have been reported.Case presentationA 12-year-old boy was diagnosed with biopsy-proven IgAN, which was characterized by heavy proteinuria and hematuria. Additionally, MAS was found by performing abdominal computed tomography angiography (CTA) due to blood pressure difference between upper arm and thigh. Methylprednisolone and cyclophosphamide were used for treating IgAN. MAS was corrected with GORE-TEX Vascular Grafts (expanded polytetrafluoroethylene, ePTFE). Remission was achieved eventually. To the best of our knowledge, we are the first to report a childhood case who has IgAN concomitant with congenital MAS. We also presented a case-based review regarding the association between IgAN and vascular stenosis.ConclusionMAS is an aggravating factor and might be a new cause of secondary IgAN.